Prostaglandins and the gastric epithelium: effects of misoprostol on gastric epithelial cell proliferation in the dog. Issue 3 (March 1989) - Goodlad, R A; Madgwick, A J; Moffatt, M R; Levin, S; Allen, J L; Wright, N A
Abstract : The effects of the methyl ester analogue of prostaglandin E1, misoprostol, on gastric epithelial cell proliferation were investigated in six dogs given 300 micrograms/kg/day of misoprostol orally for 11 weeks and in six control dogs given placebo for 11 weeks. Misoprostol treatment resulted in a 36% increase in stomach weight (p less than 0.01) and a 30% increase in the length (measured as the cell column count from the base/neck junction to the surface) of the fundic gastric glands (p less than 0.01). This mucosal hyperplasia was predominantly caused by enlargement of the foveolar region of the gland, with little change occurring in the neck or in the isthmus. The hyperplasia was the result of an increased number of mitotic (p less than 0.01) and DNA synthesising cells (p less than 0.05) in each gastric gland, which resulted in a significant increase in the gland cell production rate, from 22.5 to 42.6 cells per gland per day (p less than 0.05).